Social scientists as policy makers: E. G. Malherbe and the National Bureau for Educational and Social Research, 1929-1943 - Fleisch, Brahm (My University, 1993)
This essay is a history of the origin, elaboration and implementation of this politics of knowledge in the National Bureau of Educational and Social Research. Established in 1929 as an information gathering and research division within the South African Union Department of Education, the Bureau became the center of the development of a new relationship between social science and policy in South Africa. Four years after it was founded the Bureau's potential influence increased with the substantial grant from the Carnegie Corporation of New York. This foreign funding would enable the Bureau to sponsor, conduct, and publish social science research, as well as to build a national library on educational and social sciences. Although temporarily closed in 1940 for the duration of the Second World War, the Bureau continued to exert influence on State policy until its incorporation into the Human Sciences Research Council in 1969
African Studies Seminar series. Paper presented 8 March, 1993.
Keywords: Malherbe, E. G. (Ernst Gordon), 1895-; South Africa. National Bureau of Educational and Social Research. History. Congresses; Policy sciences. Congresses; Policy scientists. South Africa. Congresses